Proteção aos refugiados nas regiões de origem: o caso da Etiópia - Andrade, Rafaela Santos (2023)
Poor countries hosts the major portion of refugees worldwide, still Europe has taken for itself the “refugee crisis” dicourse. In this regard, there is a notable pattern: poor countries shelter them while rich countries pay for their protection in the “regions of origin” (HYNDMAN, 2020). Thus, we must look critically into how the model of burden sharing has been allocated in the North-South context, chiefly after Global Compacts on Refugees implementation, which encourages funding into host countries in an attempt to share responsibility for refugees among all States. Ethiopia is one of pilot countries for this approach, as it is one of whom hosts a huge amount of displaced people and, therefore, key-piece to maintain them in the African continent. For this, will be substantial to look through the citizenship concept in a critical perpective in order to analyze the refugee while a non-citizen. Based in this previous context, this reaserch is oriented by the following question: what are the implications of Global Compact on Refugees at Ethiopia? Therefore, this research is qualitative, case-oriented, the Ethiopia. The method of approach employed is hypothetical-deductive and the research is bibliographical, substantiated by secondary sources.